Sensitization to Sitophilus granarius in selected suburban population of South Poland. (October 2016) - Jakubas-Zawalska, Justyna; Asman, Marek; Kłyś, Małgorzata; Solarz, Krzysztof
Abstract: Storage insects may cause occupational allergies in humans. The identification of the prevalence of IgE reactions were measured from protein fractions prepared from multiple life stage of granary weevil Sitophilus granarius [SG] is reported. Sera of 30 patients from a suburban population of Upper Silesia (South Poland) were tested for the presence of IgE antibodies to antigens from larvae, pupae and adults of both sexes of the beetle. To identify protein fractions containing potential allergens, proteins collected from four life stages of granary weevil were fractionated by SDS-PAGE and probed with anti-human, anti-IgE monoclonal antibodies. The proteins were fractionated by SDS PAGE and identified by Western blot. The patients' antibodies against particular antigens were identified using anti-human anti-IgE monoclonal antibody. The conducted immunological analysis showed the existence of many protein fractions for each life stage of SG which give positive reactions with IgE antibodies. The largest number of allergenic potential fractions was shown in pupae (60 protein fractions) while the smallest amount was shown in larvae (44 protein fractions). Summarizing, the obtained results suggest the existence of many protein fractions with an allergenic potential multiple life stages of SG. This indicates that all developmental stages of SG may be a serious source of antigens and potential risk factors for the exposed persons. Highlights: The identification of the prevalence of IgE reactions from protein fractions prepared from multiple life stage of granary weevil is reported. The conducted immunological analysis showed the existence of many protein fractions for each life stage of SG which give positive reactions with IgE antibodies. The results indicate that all developmental stages of this storage insect may be a serious source of antigens.